Study on the Effect of CeO2 on the Performance of WC + Ni60 Laser Cladding Coating - Jingquan Wu; Jianwen Zhang; Dianlong Chen; Jiang Huang; Wenqing Shi; Fenju An; Xianglin Wu (Lubricants)
The aim of this investigation was to examine how CeO2 powder influences the performance of WC + Ni60 composite powder. Various cladding layers of WC + Ni60, incorporating differing mass fractions of CeO2, were created on the surface of Q235 steel utilizing laser cladding technology. To analyze the microscopic structure of the resulting cladding layer, scanning electron microscopy was employed. Additionally, the abrasion and corrosion resistance properties were assessed through experimentation with a pin-and-disc friction and wear tester and an electrochemical workstation, respectively. The results of the study showed that when the mass fraction of CeO2 was 1%, the grain on the surface of the coating was refined, the carbide formation was reduced, and the uniformity of the cladding layer was the best. In terms of corrosion resistance, the coating with 1% CeO2 had a self-corrosion potential of 0.07 V and a self-corrosion current density of 1.82 × 10−5 A·cm−2, showing the best corrosion resistance, and the coating self-corrosion potential was higher than that of the coating and substrate without CeO2. In terms of abrasion resistance, coatings with 1% CeO2 had a lower coefficient of friction (0.47) and a smaller wear rate 0.034 mm3, and the wear amount was only 23.5% of that of coatings without CeO2, resulting in the best wear resistance. In conclusion, coatings containing 1% CeO2 exhibit the minimal coefficient of friction and the lowest wear rates, while simultaneously providing optimal corrosion resistance.